Optimal Contracting and Insider Trading Restrictions - Fischer, Paul E. (Journal of Finance, 1992)
Restrictions on trading by insider agents are analyzed using an optimal contracting framework. Prohibition of insider trading is shown to be Pareto preferred if, and only if, a revelation or moral hazard problem exists. If prohibition of insider trading is valuable, then trade registration with a delay is shown to be as valuable as complete prohibition. Short selling restrictions, however, are generally of less value than complete prohibition. Finally, regulation of insider agent trading by governmental institutions and/or professional associations is discussed.